Consumer Perceptions of Brand Localness and Globalness in Emerging Markets: A Cross-Cultural Context - Safeer, Asif Ali; Zhou, Yewang; Abrar, Muhammad; Luo, Fang (Frontiers in Psychology, 2022)
The globalization of markets and consumer behavior has changed dramatically in recent years. Similarly, global and local brands are facing many challenges in emerging markets. Thus, in this backdrop, this research is intended to examine the impact of consumer perceptions of brand localness and globalness on brand attitude in order to predict consumer behavioral intentions (purchase intention, price premium, and word of mouth) in cross-cultural emerging markets (China and Pakistan). Additionally, this research considered the moderating effects of consumer ethnocentrism and brand familiarity as a control variable. This study used an online survey to examine 1,562 responses from Chinese (n = 768) and Pakistani (n = 794) consumers regarding local and global brands. The proposed hypotheses were analyzed by using the partial least square-structural equation modeling method. The findings indicated that the consumer perceptions of brand localness and brand globalness had a substantial impact on brand attitude, which in turn favorably influenced consumer behavioral intentions in China and Pakistan. The brand attitude was a crucial mediator in both markets but was more critical in China than Pakistan. The interaction moderating effects of consumer ethnocentrism and consumer perceptions of brand localness positively influenced brand attitude in China, whereas consumer ethnocentrism and consumer perceptions of brand globalness negatively influenced brand attitude in Pakistan. Interestingly, brand familiarity was discovered a substantial control variable in both markets, except for purchase intention in Pakistan. This research contributed to Fishbein’s attitude theory and social identity theory. This research offers important recommendations to local and global marketers and brand managers in formulating and employing several positioning, market segmentation, and targeting strategies that may assist them in competing effectively in emerging markets.